Impaired lung function as a risk factor for accelerated brain ageing: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Frenzel, Stefan; Bülow, Robin; Ewert, Ralf; Habes, Mohamad; Stubbe, Beate; Voelzke, Henry; Katharina, Wittfeld; Seshadri, Sudha; Grabe, Hans J.
Abstract: Background: Poor pulmonary health is increasingly recognized as an important risk factor for accelerated brain ageing and the development of dementia. We report on associations of spirometry with MRI‐based volumetry of the brain in the large community‐based Study of Health in Pomerania Trend (SHIP‐Trend). Method: N=1651 participants of SHIP‐Trend underwent both spirometry and MRI scans of the head. Measurements of forced expiratory volume during first second (FEV1), forced vital capacity (FVC) and relative FEV1 were standardized with respect to age, sex, and body height using the GLI 2012 reference equations. T1‐weighted MRI scans were processed with FreeSurfer 5.3 and total brain volumes (TBV), total gray matter volumes (TGM), total hippocampal volumes (HV) were determined. In addition, we considered the total volume of white matter hyperintensities (WMHV) estimated from T2‐FLAIR images and a recently proposed MRI‐based Alzheimer's disease index (FSAD). Linear regressions of MRI parameters on standardized FEV1, FVC, and relative FEV1, respectively, were performed. Age, sex, intracranial volume, height, smoking status, and presence of diabetes were added as covariates to each model. Effect sizes were assessed by Cohen's f 2 . Analyses were performed using data from young‐aged (≤ 60y), old‐aged (>60y), and all participants, respectively. Result: FEV1, FVC, and relative FEV1 were significantly positively associated with greater TBV, TGM, and HV in the whole sample. WMHV was significantly negatively associated with FVC and positively associated with relative FEV1. The FSAD index was significantly negatively associated with FEV1, and FVC. Associations with FEV1 and FVC were consistently stronger in old‐aged compared to young‐aged participants. For TBV, HV, WMHV, and FSAD, effect sizes were f 2 ≈0.01. For TGM, effect sizes were f 2 ≈0.05, significantly larger than those of diabetes. No significant associations with relative FEV1 were found in the group of old‐aged participants. Conclusion: Our results suggest that impaired lung function is a risk factor for atrophy of brain tissue. In old‐aged individuals, this seems to be specifically related to restrictive spirometry patterns (i.e. reductions in FEV1 and FVC but not relative FEV1) but not obstructive ones (i.e. reductions in relative FEV1). This work was supported by the Cognitively Healthy Nonagenarians in the Cross‐Cohort Collaboration Consortium (CCC) grant AG059421.